The Natural History of Primary Inner Ear Schwannomas: Outcomes of Long-Term Follow-Up. Issue 10 (22nd December 2022) - Khera, Zain; Kay-Rivest, Emily; Friedmann, David R.; McMenomey, Sean O.; Thomas Roland, J.; Jethanamest, Daniel
Abstract : Objective: To describe the natural history of primary inner ear schwannomas over a long follow-up period. Study design: Retrospective case series. Setting: Tertiary referral center. Patients: Patients with primary inner ear schwannomas with serial audiometric and radiologic follow-up. Main Outcome Measure(s): Patterns of hearing loss, rate of hearing decline, presence of vestibular symptoms, and rate of tumor growth. Results: A total of 12 patients with 13 tumors were identified. The mean duration of follow-up was 7 years. Forty-six percent of tumors were intracochlear, 15% were intravestibular, 23% were transmodiolar, and 15% were intravestibular-cochlear. Hearing loss was the most common presenting symptom, occurring in all patients. Among patients with serviceable hearing (American Academy of Otolaryngology-Head and Neck Surgery Class A or B) at the time of presentation, the average time to decline to a nonserviceable hearing level was 57.3 months (range, 21–117 mo). Hearing loss was sudden in 31% of patients, progressive in 61% and fluctuating in 8%. No patients had intractable vertigo; however, two required vestibular physiotherapy. On initial magnetic resonance imaging, the mean largest tumor dimension was 3.1 mm (standard deviation, 1.2 mm), and the mean largest dimension on most recent magnetic resonance imaging was 4.4 mm (standard deviation, 1.1 mm). Two tumors exhibited no growth over a follow-up of 11.3 and 2.8 years, respectively. Overall, the mean growth was 0.25 mm per year followed. Two patients underwent cochlear implantation with simultaneous tumor resection and had favorable outcomes. Conclusion: Long-term follow-up suggests a conservative approach, with possible hearing rehabilitation at the time of deterioration, is a safe management strategy for primary inner ear schwannomas.